Legal Implications of Amendment to Business Competition Law Provisions in Law Number 5 of 1999 After the Enactment of the Omnibus Law - Christopher Hartono (Jurnal Ilmu Multidisiplin, 2025)
Law Number 11 of 2021 on Job Creation changes the regulations related to business competition law as regulated in Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. This amendment aims to improve the business competition climate to generate a positive impact on business actors and the community. Various issues and the development of changes to this law are presented in the form of seminars and scientific studies that carry topics on changes in business competition that need to be corrected immediately. After the enactment of the Omnibus Law, which changes the five articles of business competition, it needs to be studied with the main objective of business competition itself. This study will start by looking at the background and discussing the impact after the enactment of the new law for business actors, the community, and all related parties such as regarding the change in filing an objection to the Commercial Court. The method used in this paper is normative juridical by analyzing the applicable law and the impact that occurs. And the research approach used is a statutory approach and a conceptual approach. The result of this paper is that this change does not completely solve the problems that occur in the realm of business competition.